Transoral endoscopic thyroidectomy vestibular approach, adaptation of modern surgical technique in a developing country - Ahmad Nawaz Ahmad,; Zakir, Iqra; Hamdan Ahmed Pasha, (Journal of the Pakistan Medical Association, 2023)
Conventional thyroidectomy has been the standard technique for over 100 years but has the drawback of leaving a scar on the neck. As such, the demand for minimally invasive endoscopic thyroid surgery is rapidly growing as patients are becoming more and more worried about scars; it is more appropriate in patients who want to get surgery done because of odd looking swelling over the neck. TOETVA is safe, feasible, effective, and scar-free alternative to conventional thyroid surgery. We are sharing our first clinical experience in TOETVA in Pakistan with effective outcome in terms of surgical complication and patient satisfaction. Keywords: TOETVA, minimally thyroid surgery, Pakistan.